2011
DOI: 10.1128/aem.00679-11
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Gac Mutants of Pseudomonas Biological Control Strains: Cheaters or Mutualists?

Abstract: Bacteria rely on a range of extracellular metabolites to suppress competitors, gain access to resources, and exploit plant or animal hosts. The GacS/GacA two-component regulatory system positively controls the expression of many of these beneficial external products in pseudomonad bacteria. Natural populations often contain variants with defective Gac systems that do not produce most external products. These mutants benefit from a decreased metabolic load but do not appear to displace the wild type in nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 48 publications
(73 reference statements)
2
52
1
Order By: Relevance
“…For example, the motility of strain Pf-5 is influenced by the GacS-GacA system (16), and the predominance of Gac Ϫ mutants at the advancing edge of swarming colonies of P. protegens Pf-5 has been attributed to their hyperflagellation (17). Biofilm formation is also influenced by the GacS-GacA system (16), and Driscoll et al (23) reported evidence for a mutualism between Gac Ϫ mutant and wild-type cells of P. chlororaphis 30-84 in laboratory biofilms. Duffy and Défago (24) proposed that the osmotic potential of the medium influenced the proportion of Gac Ϫ mutants in cultures of P. protegens CHA0, recognizing that GacS-GacA influences the response of bacterial cells to environmental stress (20,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the motility of strain Pf-5 is influenced by the GacS-GacA system (16), and the predominance of Gac Ϫ mutants at the advancing edge of swarming colonies of P. protegens Pf-5 has been attributed to their hyperflagellation (17). Biofilm formation is also influenced by the GacS-GacA system (16), and Driscoll et al (23) reported evidence for a mutualism between Gac Ϫ mutant and wild-type cells of P. chlororaphis 30-84 in laboratory biofilms. Duffy and Défago (24) proposed that the osmotic potential of the medium influenced the proportion of Gac Ϫ mutants in cultures of P. protegens CHA0, recognizing that GacS-GacA influences the response of bacterial cells to environmental stress (20,27).…”
Section: Discussionmentioning
confidence: 99%
“…Given the broad influence of the GacS-GacA system on bacterial physiology, it is striking that spontaneous gacS and gacA mutants (i.e., Gac Ϫ mutants) emerge and accumulate in cultures of Pseudomonas spp. (17,(21)(22)(23)(24)(25)(26)(27). Colonies of these mutants can be distinguished from those of the wild type visually by their expanded colony size, flattened appearance, increased fluorescence under UV light, and lack of extracellular protease production (21,24).…”
mentioning
confidence: 99%
“…We believe that the insights gained from our study have implications for other public good traits for two reasons. For one thing, it was shown that public goods traits can easily be lost through SNPs in their key regulators [21,22,[34][35][36]. However, regulators are usually highly specialized proteins encoded by a single gene, such that mutational targets allowing reversion or compensation are likely limited [9,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, every function has a constitutive cost, considering both genomic content and metabolism (Giovannoni et al, 2005, Kreft andBonhoeffer, 2005;Lahti et al, 2009;Driscoll et al, 2011) but this cost is usually offset by the fitness benefits the function provides (Giovannoni et al, 2014). If a function loses its beneficial effects it will eventually be purged to reduce energy costs.…”
Section: Size Matters In the Bqhmentioning
confidence: 99%